Identification and Functional Analysis of Two Purple Acid Phosphatases AtPAP17 and AtPAP26 Involved in Salt Tolerance in Arabidopsis thaliana Plant - Abbasi-Vineh, Mohammad Ali; Sabet, Mohammad Sadegh; Karimzadeh, Ghasem (Frontiers in Plant Science, 2021)
Tolerance to salinity is a complex genetic trait including numerous physiological processes, such as metabolic pathways and gene networks; thereby, identification of genes indirectly affecting, as well as those directly influencing, is of utmost importance. In this study, we identified and elucidated the functional characterization of AtPAP17 and AtPAP26 genes, as two novel purple acid phosphatases associated with high-salt tolerance in NaCl-stressed conditions. Here, the overexpression of both genes enhanced the expression level of AtSOS1, AtSOS2, AtSOS3, AtHKT1, AtVPV1, and AtNHX1 genes, involving in the K+/Na+ homeostasis pathway. The improved expression of the genes led to facilitating intracellular Na+ homeostasis and decreasing the ion-specific damages occurred in overexpressed genotypes (OEs). An increase in potassium content and K+/Na+ ratio was observed in OE17 and OE26 genotypes as well; however, lower content of sodium accumulated in these plants at 150 mM NaCl. The overexpression of these two genes resulted in the upregulation of the activity of the catalase, guaiacol peroxidase, and ascorbate peroxidase. Consequently, the overexpressed plants showed the lower levels of hydrogen peroxide where the lowest amount of lipid peroxidation occurred in these lines. Besides the oxidation resistance, the boost of the osmotic regulation through the increased proline and glycine-betaine coupled with a higher content of pigments and carbohydrates resulted in significantly enhancing biomass production and yield in the OEs under 150 mM NaCl. High-salt stress was also responsible for a sharp induction on the expression of both PAP17 and PAP26 genes. Our results support the hypothesis that these two phosphatases are involved in plant responses to salt stress by APase activity and/or non-APase activity thereof. The overexpression of PAP17 and PAP26 could result in increasing the intracellular APase activity in both OEs, which exhibited significant increases in the total phosphate and free Pi content compared to the wild-type plants. Opposite results witnessed in mutant genotypes (Mu17, Mu26, and DM), associating with the loss of AtPAP17 and AtPAP26 functions, clearly confirmed the role of these two genes in salt tolerance. Hence, these genes can be used as candidate genes in molecular breeding approaches to improve the salinity tolerance of crop plants.